Astronomy and civilization in the new enlightenment passions of the skies - Tymieniecka, Anna-Teresa; Grandpierre, Attila (Analecta Husserliana, the yearbook of phenomenological research, 2011)
This volume represents the first which interfaces with astronomy as the fulcrum of the sciences. It gives full expression to the human passion for the skies. Advancing human civilization has unfolded and matured this passion into the comprehensive science of astronomy. Advancing science's quest for the first principles of existence meets the ontopoietic generative logos of life, the focal point of the New Enlightenment. It presents numerous perspectives illustrating how the interplay between human beings and the celestial realm has informed civilizational trends. Scholars and philosophers debate.